Imitating Ovid to the Greater Glory of God - Eickmeyer, Jost (Journal of Jesuit studies, 2014)
Between 1514 and 1663 the genre known as Heroides, coined by Ovid, was maintained almost entirely by modern Latin poets. This article considers this period, which has up to now remained almost unheeded in the history of the genre. It looks at the collections of epistles by relevant authors (Eobanus Hessus, Andreas Alenus, Jacob Bidermann, Balduinus Cabillavius, Jean Vincart, Jacob Balde) in their context within literary history and considers the various ends they served, with a focus on their representations of Jesuit history and culture. Their relations to contemporary poetological discourses, represented for example by the Jesuit scholar Antonio Possevino, are addressed as well as their use of pictural media as in the case of Jean Vincart’s heroic epistles.